Sífilis, HIV e alterações citopatológicas para a ocorrência de câncer de colo de útero - França, Lyvia Mirelle Carneiro de (2018)
Introduction: Cancer of the Uterine Cervix (CUC) is one of the diseases that afflicts women, and on average 80% of these events happen in developing countries. In Brazil, the CUC is the fourth cause of death for malignant neoplasms in female population. This pathology, usually asymptomatic is slowly progressing, where the process includes neoplastic lesions or previous neoplastic, is detected early by Papanicolau Exam (PE). Several factors are associated with, including Sexually Transmitted Infections (STI). Objective: To identify factors associated with the presence of citopatológicas changes of the cervix, HIV and/or syphilis in women who performed the PE on family health Unit San Martin, in Salvador-BA, from 02 January 2015 to 09 March 2018. Methods: This cross-sectional study consisted of 150 participants. After application of a questionnaire, was conducted clinical examination of the breast and gynecological, and quick tests for diagnosis of syphilis and HIV types 1 and 2. The bivariate analysis was made by associating each of the independent variables with the outcome, through contingency tables (Chi-square test and when necessary, the Fisher's exact test). The magnitude of the association between the presence of injury and diagnosis of syphilis was expressed by the Ratio of Prevalence (RP), 95% Confidence Interval (CI 95%) and p values. To test the difference of averages was used the Student's t-test. Results: The group with injury presented the worst values in relation to the use of the breast to change cigarette palpation and papillary discharge, in comparison to the group without precursor lesion pro CUC, with statistically significant (p≤0.05). In addition, the present results showed a statistically significant association between syphilis and unloading mammary papillary (ORbruta=0.05; IC 95% [1.00-> 99.9]). Discussion: The study confirmed risk factors for precursor lesion of CUC and to syphilis existing ones, the example of smoking and mammary, changes for injuries, and level of education for syphilis, as well as diverged as research related to the use of condom and decreasing the risk of injury and the likely association with the STI. Conclusions: The precursor lesion of the CUC was a factor associated with syphilis. Were not cases of HIV types 1 and 2 in the sample. Less expected findings were observed in this study, the relationship between hypertension and papillary discharge and the presence of syphilis.